Digital Inclusion in New Zealand - Maggie Hartnett; Alison Fields (Flexible Learning Association of New Zealand, 2020)
Digital inclusion-having what we need to participate in, contribute to, and succeed in the digital world-is becoming a priority for individuals, groups, and governments around the world. Not having the necessary motivation, access, skills, and trust to engage with all things digital can result in both individuals and groups being digitally excluded. In this Editorial we look at what is encompassed by digital inclusion, who is most likely to be excluded, and the New Zealand government's recent publication of the Digital Inclusion Blueprint. Following this discussion, the papers included in this issue are introduced.